EFFECTIVENESS OF PHYSICAL THERAPY SERVICES THROUGH TELEMEDICINE DURING THE COVID-19 PANDEMIC: SYSTEMATIC REVIEW - Viorentina Yofiani; Amal Chalik Sjaaf (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
The Covid-19 pandemic has greatly impacted physical therapy services. In the context of the physical distancing strategy, physical therapy services at health care centers are very limited. Telemedicine or telerehabilitation offers a solution that is expected to be realized by physical therapy services so that it can be accessed by patients with impaired function and movement from home and can reduce the risk of the getting Covid-19 virus infection during this pandemic. This study aims to systematically review the effectiveness of physical therapy services through telemedicine or telerehabilitation during Covid-19 pandemic. The method used is a systematic review done by searching for articles from Science Direct, Scopus, and Proquest with the keywords "Effective AND Physical Therapy AND Telemedicine OR Telerehabilitation AND Coronavirus". The inclusion criteria are articles published from April 2020 to April 2021, full-text articles, and in English. Research subjects are physical therapy patients who use telemedicine or telerehabilitation. The exclusion criteria were articles that had topics outside of physical therapy services through telemedicine or telerehabilitation during the Covid-19 pandemic. The literature search yielded 30 potential articles and 8 of them met the eligibility criteria. All selected studies show that physical therapy services through telemedicine or telerehabilitation have a good result on the recovery process of movement and body function of patients with cardiorespiratory, musculoskeletal, and neuromuscular disorders during the Covid-19 pandemic. This method of remote health care delivery allows patients to carry out an exercise program at home and reduces their risk of getting Covid-19 virus infection.Â